On Hamel’s equations - Zenkov Dmitry V. (Theoretical and Applied Mechanics, 2016)
This paper reviews recent results on the extension of Hame’s formalism to infinite-dimensional mechanical systems and to variational integrators. Of a particular interest are applications to the dynamics and numerical integration of systems with velocity constraints.